2018
DOI: 10.1080/15384101.2018.1444236
|View full text |Cite
|
Sign up to set email alerts
|

Role of FcαR EC2 region in extracellular membrane localization

Abstract: The FcαR receptor (CD89) binds to the constant region of Immunoglobulin (Ig) A to mediate mucosal immunity [1-2]. FcαR consist of five exons: two that code for the signal peptide regions S1 & S2, two for the extracellular regions EC1 and EC2, and the final exon for the transmembrane/cytoplasmic tail region [3]. Previously, we reported that the EC1 region plays an essential role for extracellular membrane localization of the receptor [4], where the absence of EC1 would prevent the variants from localizing to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

7
0

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Fab or Fv, and not on IgA. Thus, together with our other findings [26,27,45,46] also involving other proteins, we have shown the need to examine proteins as a whole for more comprehensive holistic investigations, especially on allostery. In particular to the context of whole antibody, we found the hinge rigidity and the allosteric communications between the distant constant and variable regions both to contribute to antigen binding.…”
Section: Discussionsupporting
confidence: 54%
“…Fab or Fv, and not on IgA. Thus, together with our other findings [26,27,45,46] also involving other proteins, we have shown the need to examine proteins as a whole for more comprehensive holistic investigations, especially on allostery. In particular to the context of whole antibody, we found the hinge rigidity and the allosteric communications between the distant constant and variable regions both to contribute to antigen binding.…”
Section: Discussionsupporting
confidence: 54%
“…It should also be noted that many of these previous studies were performed on antibody fragments, e.g., Fab or Fv, or on IgG, and not on the whole IgA. Thus, together with our other findings [25,26,46,47] also involving other proteins, we have shown the need to examine proteins as a whole for comprehensive holistic investigations, especially on allostery. In the context of the whole antibody, we found that the hinge rigidity and the allosteric communications between the distant constant and variable regions both contribute to antigen binding.…”
Section: Discussionmentioning
confidence: 49%
“…In-house competent E. coli DH5a cells were chemically transformed 16 with two ampicillin-resistant plasmids, pTT5 17 and pET21d (Thermo Fisher Scientific, Singapore). These plasmids hold the following gene inserts: HIV-1 protease (Hprot, accession number: AY622223.1), HIV-1 Gag (Hgag 18 ), human CD89 (Fc fragment of IgA receptor FCAR, accession number: NM_002000.4, 19,20 ), and human CD32 (Fc fragment of IgG receptor IIa FCG2A, accession number: NM_001136219.3 21 ).…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%